Knowledge, attitude, and behaviour of patients and pharmacists towards cough and its treatment: a questionnaire-based Pan-India survey - Prabhudesai, Pralhad (International Journal Of Community Medicine And Public Health, 2018)
Background: Cough is one of the most common symptoms for which medical treatment is sought in the outpatient setting. An increased awareness of treatment patterns for the management of cough among pharmacists and patients is essential for its effective management and improving patients' quality of life. Considering the paucity of data from India, present survey was conducted to assess the knowledge, attitude, and behaviour (KAB) regarding cough management among patients and pharmacists in Indian setting. Methods: Patients and pharmacists (≥18 years) were provided with a questionnaire-based survey with domains namely knowledge (patients: 11; pharmacists: 10 questions), attitude (patients: 7; pharmacists: 9 questions), and behaviour and experience (patients: 15; pharmacists: 13 questions). Results: 1000 patients (men: 75%; mean age: 33.85±10.77 years) and 50 pharmacists (men: 100%; mean age: 38.36±10.64 years) completed the survey. The mean knowledge domain scores were moderate for patients (5.66±2.94) and low for pharmacists (3.34 ±2.95). About 31% patients and 72% pharmacists had low knowledge level. The mean attitude domain scores were also low among both the groups (patients: 4.81±3.34; pharmacists: 5.10±4.16). Majority of patients (96%) purchased cough medicines multiple times in a year; ~60% purchased without consulting a physician. Most patients purchased medicines without a prescription (94%) or using an old prescription (88%); but only 12% patients received advice on dosing from the pharmacist. OTC medicines were dispensed to paediatric (up to 30%) and elderly patients (up to 16%) as well. Conclusions:Knowledge and attitude regarding cough and its management is not adequate among patients and pharmacists, which in turn had a negative impact on their behaviour. This study emphasizes the need for awareness programs and healthcare policies for the effective management of cough.